Study on Economics of Corruption; Implications for Economic Disruptions and Agricultural Inefficiency in Nigeria - E. E. Osuji; A. C. Tim-Ashama; C. C. Ibekwe; J. N. Obi; E. U. Eze; U. A. Essien; C. L. Njoku (New Innovations in Economics, Business and Management Vol. 4, 2022)
Corruption is a socio-economic phenomenon which has eaten deep into the fabrics of the Nigerian economy and thus adversely affecting various sectors of the economy and most importantly the agricultural sector which is being rendered comatose, thus study on economics of corruption; implications for economic disruptions and agricultural inefficiency in Nigeria were reviewed. Causes of corruption in Nigeria include; poverty, greed, self-interest, insatiable wants, covetousness, quest to power, etc. Income inequality, bureaucracy: job insecurity, inordinate societal values, etc were its economic indices. Economic consequences of corruption in Nigeria range from slow pace of economic growth, increase in investment costs, decrease in gross domestic product, effects on employment, balance on payment effects, etc. Eradicating corruption in Nigeria calls for serious concerns and following the recommendations such as; increase in cost of corruption, elimination of corruption incentives, provision of basic needs, job security, etc. Corruption in Nigeria will be a thing of the past.